Projectile launch: a proposal based on three pedagogical moments (Research, Society and Development, 2020)
This article refers to a didactic proposal related to projectile launching, whose theoretical pillar is Ausubel's Theory of Meaningful Learning. The stages were structured according to The Three Moments of Education, by Delizoicov and Angotti. The objective was to teach concepts of the oblique movement with greater participation and interaction of students in the teaching and learning process. The proposal includes videos that show the practical application of the concepts involved, the construction of a launcher and its use in some challenging activities. The proposal was carried out, in seven classes, in the context of basic education with students from the 1st year of high school in a public school. The results point to positive signs in the students' learning, since at the beginning most of the answers, in the pre-test, were blank, while in the post-test, applied at the end of the proposal, a greater number of correct answers was observed.